Consuming television : television and its audience. - Mullan, Bob. (Oxford, UK ; Cambridge, Mass. : Blackwell, 1997)
Audiences. Technology. Programmes. 'Quality television'. News. Television, politics and impartiality. Offensive television. Children, regulation and the 'effects' of television. Television's uncertain future.
Keywords: Television viewers; Television viewers; Television programs; Television broadcasting